Wellbeing in higher education cultivating a healthy lifestyle among faculty and students - Henning, Marcus 1957-; Krägeloh, Christian U.; Dryer, Rachel; Moir, Fiona (Routledge research in educational psychology, 2018)
"Academic staff and students within higher education settings are confronted by a learning environment that is academically stimulating, informative, career-focused and socially rich, which can be intensely competitive and highly charged. Within this learning environment, academic staff and students are often at risk of compromising their wellbeing in their pursuit of academic excellence. This book provides an examination of the key areas that are important to the sustenance of wellbeing within higher education settings, with a view to promoting healthy learning environments. The chapter authors are predominantly working in the Asia-Pacific rim, but the book also includes more universal perspectives. The synthesis of the issues covered in the book is crucial to the understanding of higher education as not only an environment for gaining knowledge and skills relevant for success in academic and career domains, but also as an environment for developing socially adept and authentic communication skills. The ideas presented in this book will further assist academic staff and students to consider ways to more fully participate in their learning environment so that they can optimize their valuable contributions to the professional communities they serve"--